2011
DOI: 10.1007/978-1-61779-340-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Measles Virus Retargeting by Ligand Display

Abstract: Despite significant advances in recent years, treatment of metastatic malignancies remains a significant challenge. There is an urgent need for development of novel therapeutic approaches. Virotherapy approaches have considerable potential and among them measles virus (MV) vaccine strains have emerged as one of the most promising oncolytic platforms. Retargeted MV strains deriving from the Edmonston vaccine lineage (MV-Edm) have shown comparable antitumor efficacy to unmodified strains against receptor express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…We have recently proposed a Phase 1 clinical trial investigating the use of oncolytic MV to treat recurrent medulloblastoma. While we foresee no complications with MV-associated toxicity, additional measures to further restrict MV replication to tumor cells are available should they be deemed necessary [51,52]. …”
Section: Discussionmentioning
confidence: 99%
“…We have recently proposed a Phase 1 clinical trial investigating the use of oncolytic MV to treat recurrent medulloblastoma. While we foresee no complications with MV-associated toxicity, additional measures to further restrict MV replication to tumor cells are available should they be deemed necessary [51,52]. …”
Section: Discussionmentioning
confidence: 99%
“…Of note, Leonard et al have demonstrated that the substitution of tyrosine by alanine at position 543 (Y543A) of the wild-type H protein will render the MV selectively blind to the Nectin-4 receptor [99]. Targeting molecules such as single chain antibodies, cytokines and peptide ligands may be displayed on the C-terminus of the H protein (Table 1) [48, 100, 101]. …”
Section: Engineering Tumor Selectivity Of Oncolytic Measles Virus mentioning
confidence: 99%
“…Vaccine strain measles viruses (MVs) have substantial antitumor activity in multiple tumor entities while causing minimal damage to nonmalignant cells. At present, oncolytic MVs are under investigation in clinical trials for the treatment of ovarian cancer, glioma, and multiple myeloma, and no dose-limiting toxicity has been observed so far (Galanis et al, 2010;Msaouel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%